Teachers' made writing assessment instrument: Pedagogical insight from process to product - Khusnul Khotimah; Deisyi Anna Batunan; Nur Mukminatien (Universitas Syiah Kuala, 2024)
Despite the urgency of assessment instruments in teaching foreign language writing, evidence regarding how teachers develop assessment instruments and maintain their quality, particularly for comparison and contrast essay writing based on a genre-based approach to teachers' classroom practices, is scantily reported. To address this empirical need, this article showcases how a set of teacher-made assessment instruments for a comparison and contrast essay based on a genre-based approach in a writing essay course at a public university in East Java was carefully and deliberately developed. To attain the research objective, this research enacted design-based research (DBR) inspired by Cavallaro and Sembiante (2021). In addition to content validity, face validity and inter-rater reliability were ensured by involving ten students, three fellow writing teachers, and two trained raters. This assessment instrument development project produces a set of valid formative assessment instruments, comprising a writing prompt and scoring rubric. The inter-rater reliability shows a high degree of positive correlation with a reliability coefficient of 0.862 from a correlational analysis based on Pearson correlation coefficient. This in-practice assessment instrument development can be used as a reference, contributing to the teachers' assessment literacy development. It also serves as a valuable model for future researchers to develop and expand nested classroom assessment scholarship. A well-structured validity and reliability process of assessment instrument development will practically enhance the teaching practices in the essay writing course in particular and EFL teaching in general.